Endocrine system involvement in patients with RASopathies: A case series - Siano, M. A.; Pivonello, R.; Salerno, M.; Falco, M.; Mauro, C.; De Brasi, D.; Klain, A.; Sestito, S.; De Luca, A.; Pinna, V.; Simeoli, C.; Concolino, D.; et al. (Frontiers in Endocrinology, 2022)
Background and Objectives. Endocrine complications have been described in patients affected by RASopathies but no systematic assessment has been reported. In this study, we investigate the prevalence of endocrine disorders in a consecutive unselected cohort of patients with RASopathies. Study Design. 72 patients with a genetically confirmed RASopathy (Noonan syndrome [NS], N=53; 29 LEOPARD syndrome [LS], N=2; cardiofaciocutaneous syndrome [CFCS], N=14; subjects showing co-occurring pathogenic variants in PTPN11 and NF1, N=3) and an age- and sex-matched healthy controls were included in the study. Endocrine system involvement was investigated by assessing the thyroid function, pubertal development, auxological parameters, adrenal function and bone metabolism. Results. Short stature was detected in 40% and 64% of the NS and CFCS subcohorts, respectively. Patients showed lower Z-scores at DXA than controls (p<0.05) when considering the entire case load and both NS and CFCS groups. Vitamin D and Calcitonin levels were significantly lower (p< 0.01), Parathormone levels significantly higher (p<0.05) in patients compared to the control group (p<0.05). Patients with lower BMD showed reduced physical activity and joint pain. Finally, anti-TPO antibody levels were significantly higher in patients than in controls when considering the entire case load and both NS and CFCS groups. Conclusions. The collected data demonstrate a high prevalence of thyroid autoimmunity, confirming an increased risk to develop autoimmune disorders both in NS and CFCS. Reduced BMD, probably associated to reduced physical activity and inflammatory cytokines, also occurs. These findings are expected to have implications for the follow-up and prevention of osteopenia/osteoporosis in both NS and CFCS.